2022
DOI: 10.1038/s41598-021-04049-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive metabolomics biomarkers of production efficiency and beef carcass quality traits

Abstract: The inter-cattle growth variations stem from the interaction of many metabolic processes making animal selection difficult. We hypothesized that growth could be predicted using metabolomics. Urinary biomarkers of cattle feed efficiency were explored using mass spectrometry-based untargeted and targeted metabolomics. Feed intake and weight-gain was measured in steers (n = 75) on forage-based growing rations (stage-1, 84 days) followed by high-concentrate finishing rations (stage-2, 84 days). Urine from days 0, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Until 2023, there were 153 publications on metabolomics approaches in research with bovine species available [ 22 ]. Recently published studies predominantly aimed to identify biomarkers for desirable economic traits, such as feed efficiency [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], growth potential [ 31 ] and dairy production [ 32 , 33 , 34 ]. Metabolomics studies on the effect of supplementing RPMET to dairy/beef diets are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Until 2023, there were 153 publications on metabolomics approaches in research with bovine species available [ 22 ]. Recently published studies predominantly aimed to identify biomarkers for desirable economic traits, such as feed efficiency [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], growth potential [ 31 ] and dairy production [ 32 , 33 , 34 ]. Metabolomics studies on the effect of supplementing RPMET to dairy/beef diets are limited.…”
Section: Discussionmentioning
confidence: 99%
“…One advantage of profiling metabolites is exploring the impact of metabolism on systemic health by monitoring the production and further metabolism of compounds present in the diet, digesta, and plasma (Seidel et al, 2014). It can also be used to evaluate feed Martin et al, 2021;Artegoitia et al, 2022). Studies have also shown that the heritability of water-soluble compounds such as free amino acids, nucleotides, and sugars in beef was less than 0.30 and varied with animal age (Sakuma et al, 2016).…”
Section: Metabolomicsmentioning
confidence: 99%
“…They are the last response of biological systems to genetic and environmental effects before the expression of the phenotype, and are therefore considered as an intermediate phenotype 13 . Hence, the analysis of the metabolomic pro le can be used to study the biological mechanisms controlling the development of complex traits, as it has been shown by several authors [14][15][16][17] . A metabolomic analysis on these divergent lines will allow to take a closer look into the biological mechanisms responsible for the fat deposition, giving relevant insights that can be extrapolated to the study of obesity.…”
Section: Introductionmentioning
confidence: 99%